Abdominal wall yolk sac tumor in a child - Manasa Reddy; Pritam Singha Roy; Prema Menon; Shailesh Solanki; Shruti Gupta; Ram Samujh; Amita Trehan (Wolters Kluwer Medknow Publications, 2022)
Midline vascular abdominal wall lesions are likely to be mistaken for vascular malformations in young children. We report a case of large yolk sac tumor located in the anterior abdominal wall just below xiphisternum in a 20-month-old girl diagnosed by raised serum alpha fetoprotein levels and fine-needle aspiration cytology. Preoperative chemotherapy helped in reducing its size allowing wide resection and primary wound closure. This case is reported for the unusual location and role of chemotherapy in management.